The archaeology of Greater Nicoya : two decades of research in Nicaragua and Costa Rica - Steinbrenner, Larry; Geurds, Alexander, 1974-; McCafferty, Geoffrey G.; Salgado González, Silvia (University Press of Colorado, 2021)
"Provides an overview of this archaeological subarea encompassing Pacific Nicaragua and northwestern Costa Rica. Colonized by diverse peoples of Mesoamerican origin centuries before the arrival of Europeans, Greater Nicoya remains controversial in the twenty-first century as scholars struggle to achieve consensus on questions of geography, chronology, and cultural identity" --